WOMENS RECEPTION ON SOCIAL SUPPORT IN INSTAGRAM ACCOUNT @gethappy.id - Sari Monik Agustin; Agatha Josephine (Universitas Prof. Dr. Moestopo (Beragama), 2020)
Previous research also shows that social media has positive and negative roles related to interpersonal relationships and mental health. The social media used significantly increases social capital and mental well-being, which benefits people with low self-esteem and life satisfaction. Some psychotherapists even use an Instagram platform as their therapeutic medium. This preliminary study frameworks are Stuart Halls reception theory, the concept elaborations of social support and online social support, as well as a discussion of the character of social media, Instagram. This paper is based on a qualitative research with data from interviews with 3 female informants on 20-29 years old and gethappy.id account followers. This research succeeded in identifying 2 receptions that emerged from the female group of Instagram account followers gethappy.id. The dominant reader comes from informants who have severe physical health problems and mental health problems related to these physical health problems. Meanwhile, negotiating reader arise from informants who do not have personal physical and mental health problems, but who have a social environment with physical and mental health problems. Another important finding is that the main social support remains family and friends. Social media support is needed when the two main social supports are not present.